Assisting Indigent Families in Conflict: A Pro Bono Test Drive for a Family Alternative Dispute Resolution (ADR) Clinic - Kimberly C. Emery (Washington University Journal of Law & Policy, 2010)
In this Essay, Emery provides a case study of the formation of a robust, interdisciplinary mediation and collaborative law clinic for families who cannot afford to purchase dispute resolution. The clinic evolved out of a pro bono project for students into an academic clinic that serves to both provide access to justice and teach students important lessons regarding justice and client autonomy. This program provides a great deal of context, preparation, and training for the students, modeling high levels of professionalism and knowledge about the social justice issues surrounding poverty, domestic violence, and access to justice. The coupling of meditation and collaborative law alternatives for the clients also teaches the students about the wisdom of their clients in resolving their own problems and, with counseling, choosing the best mechanism for themselves. At the same time, the students learn important lessons about how attorneys can assist clients in resolving disputes and how interdisciplinary approaches to what appear to be legal problems enhance outcomes for clients and learning opportunities for the students.
Keywords: Domestic relations; Legal assistance to the poor; Dispute resolution (Law); Clinical legal education; University of Virginia. School of Law; Pro bono legal services; Family mediation